2014
DOI: 10.3109/00016357.2014.882983
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss and cognitive functions among older adults

Abstract: The findings suggest that the presence of teeth may be of importance for cognitive abilities in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…Our data showed that tooth loss was not associated with CI, while NRLT was associated with CI. An American study and Swedish study showed that severe tooth loss was associated with CI, while moderate tooth loss was not (Naorungroj et al, ; Nilsson, Berglund, & Renvert, ). A Brazilian study showed that tooth loss is associated with severe CI and age modifies the association between tooth loss and cognition among older Brazilian people (Peres et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that tooth loss was not associated with CI, while NRLT was associated with CI. An American study and Swedish study showed that severe tooth loss was associated with CI, while moderate tooth loss was not (Naorungroj et al, ; Nilsson, Berglund, & Renvert, ). A Brazilian study showed that tooth loss is associated with severe CI and age modifies the association between tooth loss and cognition among older Brazilian people (Peres et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the brain ages, the plasticity of the brain decreases [31,32], and it is theorized that further shocks to the brain's functions by major DDs that cause chronic dysfunctional or impaired mastication (such as the loss of strategic molars, generalized periodontal detachments and/or orthodontic management) may result in the brain's suffering varying degrees of impact in different areas. In the aging process, multiple major DDs and consequent effects may lead to blunted sensory perceptions [7–11], and cognitive and memory impairment in old age [12–30,41–53,63–65], thus contributing to the onset or aggravation of dementia or AD.…”
Section: Discussionmentioning
confidence: 99%
“…DD is shown by both animal and clinical researches to have a positive association with memory and cognitive status [12–30,41–53,63–65]. The conversion rate from MCI to dementia is reportedly 20–50% within 5 years [66,67].…”
Section: Dd and Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations